Measuring English Abilities of Junior High School Students - Afnida, Liza; Adani, Sukri (Universitas Pahlawan Tuanku Tambusai, 2024)
Students’ problems in learning English often stem from a lack of exposure to the language, insufficient practice opportunities, and challenges with grammar and vocabulary, which collectively hinder their overall proficiency and confidence. The purpose of this study is to measure students’ ability in mastering English. The method used in this study is a descriptive quantitative approach, conducted at SMP Negeri 3 Kuala Batee. The total number of participants was 27 students, and the data were collected using a test with 50 questions. The results of the study indicated that the students’ ability in mastering English was classified into high, moderate, and low categories. High abilities were evident in mastering main idea identification, understanding text purposes, and recognizing text types. Moderate abilities were observed in conversational skills, identifying supporting details in reading, pronoun reference, passive voice, and word meanings. Low abilities were noted in expressing congratulations and hope, understanding text structure and genres, conversations, simple past tense, comprehension of advertisements, word meanings, and using